Computed tomography in neurocysticercosis a 10-year long evolution analysis of 100 patients with an appraisal of a new classification - L. R. Machado; J. P. S. Nobrega; N. G. Barros; J. A. Livramento; L. A. Bacheschi; A. Spina -França (Arquivos de Neuro-Psiquiatria)
Three hundred land fifty seven computed tomography (CT) from 100 different patients with neurocysticercosis (NC) were studied between 1979 and 1988. All patients were treated with praziquantel (PZQ). A new classification attempting to recognize the CT evolution profile in NC as well as assigning a possible link between CT findings and biological conditions of cysts is evaluated. It was possible to conclude that: intact cysts remain unchanged in consecutive CTs by 11 months and exhibit signs of degeneration in about 18 months after PZQ drug therapy; degenerating cysts can be detected by 10.5 months, disappear in 11 months and become nodular calcifications in about 25 months. Therefore, a time period of at least 36 months can be estimated for the complete evolution profile of cysts in the brain parenchyma.